Study of perioperative factors in postoperative chronicity of sternal pain (Nepal Medical College Journal, 2023)
Over two million people undergo sternotomy worldwide for heart surgery each year, and post operative sternal pain may last for months or reappears a long time after sternotomy. The exact etiology of post sternotomy pain is unknown. We aim to find out the association of peri-operative factors with chronicity of sternal pain after open-heart surgery. This is a retrospective observational study on 121 patients who underwent open heart surgeries for various cardiac problems from January 2020 to July 2022 at a tertiary care center. Convenient sampling was performed. Data were analyzed using SPSS-17. Male to female ratio similar with male 60 (49.6%) and female 61 (50.4%), and 95.0% had body mass index (kg/m2)